Nonlinear L k l operator related to the Bessel-Helmholtz operator and the Bessel Klein-Gordon operator - Bunpog C. (2017)
In this article, we study the solution of the nonlinear equation where L k l is defined by and (Δ B + a 2 ) k and (□ B + b 2 ) l are defined by (2) and (3) respectively. u is an unknown generalized function and f is a given generalized function. It is found that the existence of the solution u(x) of such an equation depends on the condition of f and L k-1 l u(x). Moreover such a solution u(x) is related to the fundamental solution of Bessel-Helmholtz Operator and the Bessel Klein-Gordon Operator.